Teachers’ perceived usefulness, ease of use, and challenges with e-learning utilization sustainability after COVID-19 pandemic in Oyo state, Nigeria - Badmus, Ayodeji Muideen (Journal of Education in Black Sea Region, 2022)
This study examined teachers’ perceived usefulness, ease of use, and challenges with e-learning utilization sustainability after COVID-19 pandemic. The research was designed as a descriptive survey research and purposive sampling technique was used to select 30 schools and 300 teachers from 630 secondary schools in Oyo State in Nigeria. A questionnaire was developed tagged as teachers’ perceptions on sustainable utilization of e-learning after COVID-19 pandemic with a 0.82 reliability index obtained. The data collected were analyzed using simple percentage, mean scores, and standard deviation. The results revealed that teachers’ perceived usefulness and ease of use of e-learning were positive and high. In addition, the study has reported that some factors like irregular network service, no direct training for teachers, and many others were identified as challenges to the use of e-learning for instructional delivery. It was recommended among others that policymakers should infuse e-learning instructional strategy into the curriculum for teaching/learning process.